Imaginal Action: Towards a Jungian Conception of Enactment, and an Extraverted Counterpart to Active Imagination - Brown, Robin S. (Journal of analytical psychology, 2018)
This theoretical paper considers the fashion in which Jung's psychology radically challenges modern assumptions concerning the nature of subjectivity. With an eye for the clinical implications of Jung's late work, the author introduces the idea of imaginal action. In order to explain what is meant by this, the paper begins by exploring how Jung's thinking demonstrates an underlying bias towards introversion. It is argued that while Jung's interest in synchronicity ultimately resulted in his developing a worldview that might address the introverted biases of his psychology, the clinical implications of this shift have not been sufficiently clarified. With reference to some short examples from experience, the author outlines a conception of relational synchronicity wherein the intrapsychic emerges non-projectively within the interpersonal field itself. Comparing and contrasting these occurrences to the more introverted practice of active imagination, it is claimed that such a notion is implicit in Jung's work and is needed as a corrective to his emphasis on interiority. The author suggests that imaginal action might be conceived as a distinctly Jungian approach to the psychoanalytic notion of enactment. It is also shown how the idea outlined might find further support from recent developments in the field of transpersonal psychology.